Heme oxygenase-2/adiponectin protein–protein interaction in metabolic syndrome - Vanella, Luca; Li Volti, Giovanni; Guccione, Salvatore; Rappazzo, Giancarlo; Salvo, Eliana; Pappalardo, Morena; Forte, Stefano; Schwartzman, Michal L.; Abraham, Nader G. (Biochemical and biophysical research communications, 2013)
► HO-2 knockout mice present a metabolic syndrome-like phenotype. ► Inhibition of both HO-1 and HO-2 decreased adiponectin formation. ► Existence of protein–protein interaction between adiponectin and HO-2. ► HO-2 acts as a molecular chaperone. ► Increasing information on protein–protein complexes will lead to the designing of new drugs. Insulin resistance with adipose tissue dysfunction and dysregulation in the production and secretion of adipokines is one of the hallmarks of metabolic syndrome. We have previously reported that increased levels of the heme oxygenase (HO) system, HO-1/HO-2 results in increased levels of adiponectin. Despite documentation of the existence of the anti-inflammatory axis HO-adiponectin, a possible protein–protein interaction between HO and adiponectin has not been examined. Here, we investigated the existence of protein interactions between HO-2 and adiponectin in the maintenance of adipocyte function during metabolic syndrome by integrating phenotypic and in silico studies. Compared to WT animals, HO-2 null mice displayed an increase in both visceral and subcutaneous fat content and reduced circulating adiponectin levels. The decrease in adiponectin was reversed by upregulation of HO-1. HO-2 depletion was associated with increased adipogenesis in cultured mesenchymal stem cells (MSCs) and decreased adiponectin levels in the culture media. In addition, HO-1 siRNA decreased adiponectin release. HO-2 was found to bind to the monomeric form of adiponectin, according to poses and calculated energies. HO-2-adiponectin interactions were validated by the two-hybrid system assay. In conclusion, protein–protein interactions between HO-2 and adiponectin highlight the role of HO-2 as a molecular chaperone for adiponectin assembly, while HO-1 increases adiponectin levels. Thus, crosstalk between HO-2 and HO-1 could be manipulated in a therapeutic approach to ameliorate the deleterious effects of obesity and the metabolic syndrome.